2018
DOI: 10.1155/2018/1787424
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Based on Systemic Immune-Inflammation Index to Predict Overall Survival in Gastric Cancer Patients

Abstract: Background The systemic immune-inflammation index (SII), based on peripheral lymphocytes, neutrophils, and platelet count, has been used as a prognostic marker for several tumors. However, use of the SII has not been reported for gastric cancer. Methods We evaluated the prognostic value of the SII in primary and validation cohorts. We also established an effective prognostic nomogram for gastric cancer based on R language. The predictive accuracy and discriminative ability of the nomogram were determined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 33 publications
4
70
1
1
Order By: Relevance
“…Therefore, SII was a convenient, low-cost, and effective inflammatory indicator to predict the prognosis of tumors. Previous studies have only reported the use of SII in nomograms for gastric and tongue cancer ( 22 , 23 ). Here, we report for the first time that nomograms based on SII can effectively predict postoperative HCC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SII was a convenient, low-cost, and effective inflammatory indicator to predict the prognosis of tumors. Previous studies have only reported the use of SII in nomograms for gastric and tongue cancer ( 22 , 23 ). Here, we report for the first time that nomograms based on SII can effectively predict postoperative HCC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the importance of preoperative nutritional status and immunity in patients with GC has been recognized (5,6). The preoperative nutritional status and immunity of patients with GC determine whether the patient can undergo surgery and are some of the important factors in the evaluation of postoperative complications, postoperative recurrence and metastasis, chemotherapy tolerance and long-term prognosis (7-10).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor, Node, Metastasis (TNM) staging based on the International Union Against Cancer (UICC)/American Joint Committee on Cancer (AJCC) guidelines is currently the standard approach of determining the prognosis of GC patients [3]. However, several prognostic factors related to GC have been proposed, which include peripheral blood-derived in ammation markers, such as neutrophil-lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), systemic immune-in ammation index (SII), C-reactive protein/albumin (CRP/Alb) ratio, and Glasgow Prognostic Score (GPS) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%